SphK1/S1P mediates TGF-β1-induced proliferation of pulmonary artery smooth muscle cells and its potential mechanisms. (December 2018) - Wang, Jian; Feng, Wei; Li, Fangwei; Shi, Wenhua; Zhai, Cui; Li, Shaojun; Zhu, Yanting; Yan, Xin; Wang, Qingting; Liu, Lu; Xie, Xinming; Li, Manxiang
The upregulation of Sphingosine kinase 1 (SphK1) expression and accompanied sphingosine-1-phosphate (S1P) production have been reported to contribute to the proliferation of pulmonary artery smooth muscle cells (PASMC) and pulmonary arterial remodeling. However, the molecular mechanisms of SphK1/S1P upregulation in PASMC and the specific mechanisms of how SphK1/S1P pathway promotes PASMC proliferation remain largely unclear. This study aims to address these issues. Here, we demonstrated that TGF-β1 significantly upregulated SphK1 expression and S1P production by promoting the phosphorylation of Smad2/3 in PASMC. Further study indicated that SphK1/S1P pathway mediated TGF-β1-induced Notch3 activation in PASMC. In addition, we showed that TGF-β1 significantly induced proliferation of PASMC, while pre-inhibition of Smad2/3 phosphorylation with SB431542 or silencing SphK1 using small interfering RNA in advance, or pre-blocking Notch3 pathway with N-[N-(3, 5-difluorophenacetyl)-L-alanyl]-S-phenylglycine t-butyl ester (DAPT), attenuated TGF-β1-induced PASMC proliferation. Taken together, our study indicates that Smad2/3/SphK1/S1P/Notch3 pathway mediates TGF-β1-induced PASMC proliferation and suggests this pathway as a potential therapeutic target in the prevention and treatment of pulmonary hypertension.